2014
DOI: 10.1080/10810730.2013.872724
|View full text |Cite
|
Sign up to set email alerts
|

Does the Number of Cancer Patients' Close Social Ties Affect Cancer-Related Information Seeking Through Communication Efficacy? Testing a Mediation Model

Abstract: This study addresses the question of whether having a broad social network of close friends equips cancer patients with increased efficacy to engage in communication about their cancer, which then leads to an increased likelihood of patients’ actively seeking cancer-related information. Guided by the theory of motivated information management (TMIM: Afifi & Weiner, 2006), the study also tests whether the effect of the number of close social ties on information seeking is mediated, in part, by communication eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Within cancer communication, and particularly among partners, decreased communication efficacy is associated with increased topic avoidance of death, sexuality, and being a burden (Venetis et al, 2015). Alternatively, increased communication efficacy is associated with increased communication such as information seeking and cancerrelated conversations (Lewis & Martinez, 2014;Rauscher, 2017). Thus, we propose:…”
Section: Communication Efficacymentioning
confidence: 99%
“…Within cancer communication, and particularly among partners, decreased communication efficacy is associated with increased topic avoidance of death, sexuality, and being a burden (Venetis et al, 2015). Alternatively, increased communication efficacy is associated with increased communication such as information seeking and cancerrelated conversations (Lewis & Martinez, 2014;Rauscher, 2017). Thus, we propose:…”
Section: Communication Efficacymentioning
confidence: 99%
“…Social capital is 'actual or potential resources that result from social connections and senses of reciprocity and trust, which, when mobilised, can bring about outcomes at the individual and collective level' (Beaudoin & Tao, 2007, p. 587). Interest in the concept within the health sector is relatively recent, but research has indicated that social capital can influence health outcomes as social networks enable information and resource sharing and support (Lewis & Martinez, 2014). Close ties positively are associated with communication efficacy which then is associated with information seeking, however the relative impact of information from interpersonal versus mediated sources requires further investigation (Chen, Lee, Straubhaar, & Spence, 2014;Lewis & Martinez, 2014).…”
Section: Social Capitalmentioning
confidence: 99%
“…Interest in the concept within the health sector is relatively recent, but research has indicated that social capital can influence health outcomes as social networks enable information and resource sharing and support (Lewis & Martinez, 2014). Close ties positively are associated with communication efficacy which then is associated with information seeking, however the relative impact of information from interpersonal versus mediated sources requires further investigation (Chen, Lee, Straubhaar, & Spence, 2014;Lewis & Martinez, 2014). While social capital is widely discussed, its precise meaning, dimensions and mechanisms are unclear.…”
Section: Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Most preferred information sources are doctors, family members, nurses and friends (Pecchioni and Sparks, 2007) and such strong interpersonal networks are more likely to generate a stronger health orientation (Dutta-Bergman, 2005). Patients are usually more influenced by those with strong ties (Mair and Rikard, 2010;Lewis and Martinez, 2014). We conjecture that: H4.…”
Section: 2mentioning
confidence: 98%